Pore Structure Characteristics, Genesis, and Its Controlling Effect on Gas Migration of Quaternary Mudstone Reservoir in Qaidam Basin - Shijie He; Xianglu Tang; Zeyu Shao; Zhenxue Jiang; Bo Wang; Xiaoxue Liu; Yuchao Wang; Mingli Xu (Geofluids)
The Sanhu Depression in Qaidam Basin is the largest Quaternary biogenic gas exploration area with the shallowest burial depth in the world. The shallow high abundance of gas reservoirs and high-quality pure methane have become the main production areas. The development characteristics of loose mudstone reservoirs are restricted by extreme heterogeneity. Therefore, the Quaternary Qigequan Formation mudstone in Qaidam Basin is selected as the research object. Based on the study of the sedimentary background, petrological characteristics, and pore structure characteristics, by comparing the characteristics of different mudstone reservoirs, the controlling factors of the development of different mudstone reservoirs and the control of gas migration are clarified. Research shows the following: (1) The mudstone reservoirs of the Qigequan Formation mainly develop intergranular pores, clay mineral pores, and intragranular pores. The pore size distribution varies from nanometers to micrometers, and mesopores mainly contribute to the specific surface area. (2) Rigid minerals and clay minerals are the main controlling factors for the pore structure of mudstone reservoirs. The increase in the content of rigid minerals is conducive to the development of macropores or larger micropores, while the increase in the content of clay minerals is conducive to the development of mesopores and provides an important specific surface area for gas adsorption. (3) The gas migration form of pure mudstone is mainly dominated by Fick diffusion and slippage flow, which has the characteristics of self-sealing accumulation. The gas migration form of silty mudstone is the coexistence of Fick diffusion, slippage flow, and Darcy flow, which has the features of self-sealing and Darcy flow accumulation. The gas migration form of sandy mudstone is mainly Darcy flow, only with Darcy flow accumulation characteristics. The flow form of gas creates different accumulation modes of mudstone biogas. The Quaternary mudstone reservoir shows different particularity under different material components, and the exploration targets should be treated differently according to specific mudstone types.